New species of the genus Elachisina (Gastropoda: Elachisinidae) from northeastern Brazil - Cunha, Carlo M.; Santos, Franklin N.; Lima, Silvio F. B. (Zootaxa, 2016)
The family Elachisinidae Ponder, 1985 includes minute marine gastropods that live predominantly in the sublittoral zone (Ponder & Keyzer 1998; Rolán & Rubio 2001; Rolán & Gofas 2003). Most elachisinids have been included in the genus Elachisina Dall, 1918 based on their shell morphology (Warén 1996; Rolán & Rubio 2001; Rolán & Gofas 2003), consequently, very little is known about the habitat and ecological niche of the species (Ponder & Keyzer 1998; Rolán & Gofas 2003). Elachisina floridana (Rehder, 1943) is the only Atlantic congener collected alive, and is known to live beneath rocks and in rocky crevices in the intertidal zone to about 1 m depth in the Bahamas and Caribbean Sea (Ponder 1985; Ponder & Keyzer 1998; Rolán & Gofas 2003; Redfern 2013). Eastern Atlantic E. canarica (Nordsieck & García-Talavera, 1979) was also collected alive from the Canary Islands, but with no information on the habitat (Rolán & Gofas 2003). The islands of the northeastern Atlantic and West Africa are the regions with the greatest Elachisina richness known, totaling nine species (Rolán & Rubio 2001; Rolán & Gofas 2003). Only E. floridana has been recognized so far to be widely distributed throughout the Western Atlantic (Rolán & Gofas 2003; Rios 2009; Redfern 2013).